Arginase 1 Mediates Increased Blood Pressure and Contributes to Vascular Endothelial Dysfunction in Deoxycorticosterone Acetate-Salt Hypertension - Toque, Haroldo A.; Nunes, Kenia P.; Rojas, Modesto; Bhatta, Anil; Yao, Lin; Xu, Zhimin; Romero, Maritza J.; Webb, R. C.; Caldwell, Ruth B.; Caldwell, R. W. (Frontiers in Immunology, 2013)
Enhanced arginase (ARG) activity has been identified as a factor that reduces nitric oxide (NO) production and impairs endothelial function in vascular pathologies. Using a gene deletion model, we investigated involvement of arginase isoforms (1 and 2) in hypertension and endothelial dysfunction in a mineralocorticoid-salt mouse model. Hypertension was induced in wild type (WT), partial ARG1+/- knockout (KO) and complete ARG2-/- KO mice by uninephrectomy and DOCA-salt treatment for 6-weeks. (Control uninephrectomized mice drank tap water). After 2 wks of DOCA-salt treatment, systolic blood pressure (SBP) was increased by ~15 mmHg in all mouse genotypes. SBP continued to rise in DOCA-salt WT and ARG2-/- mice to ~130 mmHg at 5-6 wks, whereas in ARG1+/- mice SBP waned toward control levels by 6 wks (109±4 vs 101±3 mmHg, respectively). DOCA-salt treatment in WT mice increased vascular ARG activity (aorta by 1.5-fold; mesenteric artery (MA) by 2.6-fold and protein levels of ARG1 (aorta: 1.49-fold and MA: 1.73-fold) versus WT Sham tissues. ARG2 protein increased in WT DOCA MA (by 2.15-fold) but not in aorta compared to those of WT Sham tissues. Maximum endothelium-dependent vasorelaxation to acetylcholine was significantly reduced in DOCA-salt WT mice and largely or partially maintained in DOCA ARG1+/- and ARG2-/- mice vs their Sham controls. DOCA-salt augmented contractile responses to phenylephrine in aorta of all mouse genotypes. Additionally, treatment of aorta or MA from WT DOCA mice with arginase inhibitor ABH (100 µM) improved endothelium-mediated vasorelaxation. DOCA-salt induced coronary perivascular fibrosis (increased by 2.1-fold) in WT was prevented in ARG1+/- and reduced in ARG2-/- mice. In summary, arginase is involved in murine DOCA-salt induced impairment of vascular function and hypertension and may represent a novel target for antihypertensive therapy.